Concentration-Dependent Inhibitory Effect of Irbesartan on Renal Uric Acid Transporters - Makiko Nakamura; Naohiko Anzai; Promsuk Jutabha; Hiroyuki Sato; Hiroyuki Sakurai; Kimiyoshi Ichida (Elsevier, 2010)
Hyperuricemia is currently recognized as a risk factor for cardiovascular diseases. It has been reported that the angiotensin II-receptor blocker (ARB) losartan decreases serum uric acid level. In this study, the effects of another ARB, irbesartan, on [14C]uric acid-transport activity of renal uric acid reabsorptive transporters URAT1 and URATv1 were examined with Xenopus oocytes expressing each transporter. The results showed that irbesartan (100 - 500 μM) inhibited the uptake of uric acid via both transporters. The inhibitory effects of irbesartan exceeded those of losartan and other ARBs, and the results suggest that irbesartan can reduce serum uric acid level. Keywords:: angiotensin II-receptor blocker, transporter, uric acid